2016
DOI: 10.1126/science.aad5196
|View full text |Cite
|
Sign up to set email alerts
|

A DNA topoisomerase VI–like complex initiates meiotic recombination

Abstract: The SPO11 protein catalyzes the formation of meiotic DNA double strand breaks (DSBs) and is homologous to the A subunit of an archaeal topoisomerase (topo VI). Topo VI are heterotetrameric enzymes comprising two A and two B subunits; however, no topo VIB involved in meiotic recombination had been identified. We characterized a structural homolog of the archaeal topo VIB subunit [meiotic topoisomerase VIB-like (MTOPVIB)], which is essential for meiotic DSB formation. It forms a complex with the two Arabidopsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
238
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(250 citation statements)
references
References 48 publications
3
238
0
2
Order By: Relevance
“…The meiosisspecific RAD51 ortholog DMC1 is activated in glioblastoma and it contributes to proliferative potential and genotoxic stress recovery (44). In addition, during meiosis, interhomolog recombination is initiated by the type II topoisomerase-like activity of the SPO11-TOPVIBL complex, which generates a DNA doublestrand break in one participating chromatid (45)(46)(47)(48). Recent work in mice has demonstrated that the mammalian-specific gene Tex19.1 is required to promote normal levels of these meiotic recombination-initiating events (49).…”
Section: Activation Of Meiotic Functions In Cancer Cellsmentioning
confidence: 99%
“…The meiosisspecific RAD51 ortholog DMC1 is activated in glioblastoma and it contributes to proliferative potential and genotoxic stress recovery (44). In addition, during meiosis, interhomolog recombination is initiated by the type II topoisomerase-like activity of the SPO11-TOPVIBL complex, which generates a DNA doublestrand break in one participating chromatid (45)(46)(47)(48). Recent work in mice has demonstrated that the mammalian-specific gene Tex19.1 is required to promote normal levels of these meiotic recombination-initiating events (49).…”
Section: Activation Of Meiotic Functions In Cancer Cellsmentioning
confidence: 99%
“…This specific recombination pathway is initiated by the formation of DNA double-strand breaks (DSBs) (de Massy 2013) that are generated by the SPO11/TOPOVIBL protein complex (Robert et al 2016;Vrielynck et al 2016) and repaired by homologous recombination Hunter 2015). DSB repair leads to reciprocal and nonreciprocal exchanges of genetic material between paternal and maternal chromosomes, called cross-overs and gene conversions, respectively.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…AtSPO11-1 and AtSPO11-2, as subunits of a heterodimer, are essential for DSB formation whereas AtSPO11-3 is not required for DSB formation (10). Recently, an Arabidopsis homolog of the archaeal topo VIB subunit (MTOPVIB) was found to interact with the SPO11-1/2 heterodimer and participate in DSB formation (11).…”
mentioning
confidence: 99%